Cost-effectiveness of poly-(ADP-ribose) polymerase (PARP)-inhibitors for the maintenance treatment after responding to first- and second-line chemotherapy in advanced ovarian cancer. (March 2023) - Giuliani, Jacopo; Mantoan, Beatrice; Ferrario, Lucrezia; Candela, Maria Viviana; Aprile, Giuseppe
The introduction of inhibitors of poly-(ADP-ribose) polymerase (PARP) for the treatment of women with epithelial ovarian cancers (EOC) has radically changed the treatment in maintenance setting after responding to first- and second-line chemotherapy. The aim of this paper was to assess the pharmacological costs of PARP inhibitors (olaparib, niraparib, rucaparib and veliparib) in maintenance treatment after responding to first-line chemotherapy in EOC. Incremental cost-effectiveness ratio (ICER) was calculated as the ratio between the difference of the costs in the intervention and in the control groups (pharmacy costs) and the difference between the effect in the intervention and in the control groups (progression-free survival (PFS)). We have considered the pivotal phase III randomized controlled trials (RCTs). Three different populations were considered: the overall population, patients with germline BRCA mutation (gBRCA) and homologous recombination deficiency (HRD) patients non-gBRCA mutation. Three thousand four hundred and twenty patients and 1209 patients were considered in maintenance treatment after responding to first- and second-line chemotherapy in EOC, respectively. At the actual price, the treatment with PARP inhibitors is not cost-effective in maintenance treatment after responding to first-line and second-line chemotherapy in EOC. A reduction in pharmacological costs is mandatory.